The Not-So-Generalized Effects of the Generalized System of Preferences - Emanuel Ornelas; Marcos Ritel (Center for Economic Studies and ifo Institute (CESifo), 2018)
We use an empirical gravity equation approach to study how nonreciprocal trade preferences (NRTPs), enacted mainly through the Generalized System of Preferences, affect the exports of the beneficiary nations. In line with existing studies, the average trade effect stemming from nonreciprocal preferences is highly unstable across specifications. However, once we allow for heterogeneous effects, results become robust and economically important. Specifically, NRTPs have a strong effect on the exports of beneficiaries when they are members of the World Trade Organization and are very poor. Not-so-poor beneficiaries also expand foreign sales, but only if they are not WTO members. For all others, the average export effects of NRTPs are mute.
Keywords: F13; F14; F15; F55; F63; O19; O24; 330; trade preferences; gravity equation; trade policy; nonreciprocity; GSP